Implementasi Metode Lauhun dalam Meningkatkan Hafalan al-Quran Santri Pondok Pesantren Putri Hikmatun Najiyah Sidosermo Surabaya - Ulumil Ishthifaiyah; Mufaizah Mufaizah (YASIN, 2026)
The Lauhun method is a Qur’an memorization technique that emphasizes repetition through the writing of verses by students on a blackboard after the memorization recitation process. Although Qur’an memorization methods have been widely studied, studies that specifically discuss the effectiveness of the Lauhun method in improving the quality and quantity of memorization remain limited. This study aimed to examine the application of the Lauhun method in improving students’ Qur’an memorization ability at Pondok Pesantren Putri Hikmatun Najiyah Sidosermo, Surabaya. This study used a qualitative approach with a case study design. Participants were selected purposively, while data were collected through observation, in-depth interviews, and documentation. Data were analyzed using thematic analysis to obtain a comprehensive understanding of the application of the Lauhun method in Qur’an memorization learning. The results showed that the Lauhun method was able to improve the quality and quantity of students’ memorization. This improvement was reflected in the increased number of memorized verses, enhanced understanding of verse meanings, and the growth of students’ motivation and self-confidence in the memorization process. These findings indicate that the Lauhun method contributes to the development of understanding-based tahfidz learning, not merely to the quantitative strengthening of memorization. Thus, this study affirms the importance of balancing the quantity of memorization and the understanding of verse meanings in pesantren education. Practically, the Lauhun method can serve as an alternative Qur’an learning strategy in pesantren and open opportunities for further research in other Islamic education contexts.